Analisis Strategi Pemasaran Puspa Jaya Transport untuk Meningkatkan Penjualan Tiket - I Ketut Rama Arya Sentosa; Tina Miniawati Barusman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Marketing strategy is crucial for any business, whether selling goods or services. Puspa Jaya Transport, an intercity and interprovincial (AKAP) bus company, faces fluctuations in passenger numbers influenced by both internal and external factors. This study aims to analyze Puspa Jaya Transport's marketing strategy to increase ticket sales. This qualitative study used observation, interviews, and data analysis techniques, supported by a SWOT analysis and the IFAS and EFAS matrices. The results indicate that Puspa Jaya Transport is in quadrant I (growth), with strengths in service quality, punctuality, and excellent facilities, which are key strengths in utilizing digital promotional media. The recommended strategy is the SO strategy, which maximizes service quality, facilities, and digital optimization to increase ticket sales.